A study on polymerization of PVDF based fluoropolymers with high performance for battery (I) - Jo, SM; Lee, WS; Oh, HJ; Park, S; Ahn, BS; Park, KY (POLYMER SOC KOREA, 1999)
Poly(vinylidene fluoride)s(PVDFs), which were polymerized by di-t-butyl peroxide (DTBP), an initiator, at high temperature, showed low melting temperature, low crystallinity, and high contents of head-to-head inversion. The main crystal structure was cr-form (Phase II) and it showed good thermochemical stability due to their nonpolar end group. PVDF by ammonium peroxodisulfate (APS) showed higher melting temperature, higher crystallinity, and lower contents of head-to-head inversion than those by DTBP. The main crystal structures were beta-form (Phase I), but the content of alpha-form increased at high polymerization temperature. It also showed poor thermochemical stability because of their polar end group and low contents of head-to-head inversion.
Keywords: POLY(VINYLIDENE FLUORIDE)